Clinical performance of some resin-based materials in restoring non-carious cervical lesions - Diana Onet; Alexandra Roman; Iulia-Cristina Micu; Andreea Ciurea; Alina Stanomir; Stefan Cristian Vesa; Andrada Soanca; Darian Rusu (Amaltea Medical Publishing House, 2023)
Objectives. The objective of the study was to investigate the clinical performance of two different resin-based materials 6 months after their placement in dental non-carious cervical lesions (NCCL). This study also aimed to evaluate the effects of the materials on periodontal tissues in terms of clinical changes of several periodontal parameters. Material and methods. NCCLs characteristics (localization, morphology, dimensions) were preoperatively recorded. The clinical behaviour of the restorations based on the modified United States Public Health Service (USPHS) criteria and periodontal parameters (plaque index, bleeding index, probing depth, and attachment loss) were assessed at baseline and after 1, 3 and 6 months. Results. No significant modifications were recorded for the modified USPHS criteria 6 months after the placement of NCCL restorations excepting postoperative hypersensitivity which was associated with 4 restorations after 6 months. Significant improvements of plaque and bleeding indices were recorded, while no significant modifications were noted for the other periodontal parameters. Conclusions. Considering the clinical success related to the good clinical behaviour and the positive effect of the restorations on the periodontal status, the experimental conventional composites and giomers could be considered as a good therapeutic option for the restoration of NCCLs.